Pengaruh Kedalaman Potong Menggunakan Insert Radius 0,4 mm cnmg 120404n Terhadap Kekasaran Permukaan (Surface Roughness) Baja Karbon S45C - Febrianton, Adi; Putri, Indah Purnama; Romiyadi, Romiyadi; Irwan, Purnama; Sihotang, Psalmen (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
In the practical and sophisticated world of the manufacturing industry, the best product results are needed. To answer market needs that want products with maximum results and produce them in a short time, the non-conventional Computer Numerical Controlled Lathe (CNC) is available as a machine tool production tool that is controlled using a computer system to cut workpieces which are rotated to determine the roughness value on the workpiece surface. The aim of this research is to obtain the lowest surface roughness results. Using S45C carbon steel material with Sumitomo CNMG 120404-N-Gu-AC8025 brand insert with a Radius of 0.4 mm on the SKT 160A CNC Turning machine. The next process is the process of turning the workpiece with variations in cutting depth of 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm , 0.9mm, 1.0mm, 1.1mm. Using the G96 program code, the feed movement is 0.15 mm/rev with a constant spindle speed of 2700 rpm and using a Stylus as a measure of surface roughness value. By carrying out 1 test on 11 samples, each sample consisting of 3 test points. Based on the results of surface roughness data, the lowest average Ra roughness results for an insert radius of 0.4 mm were 1,115 µm at a cutting depth of 0.6 mm and was included in the roughness tolerance value N6.